Intensity-modulated Radiotherapy Planning at Mediastinal Lymphoma Treatment: Sandglass, Rainbow and Butterfly Techniques - Yucel, Serap; Gural, Zeynep; Agaoglu, Fulya (KARE PUBL, 2022)
OBJECTIVE We developed ``sandglass{''} technique using volumetric arc therapy (VMAT) with two avoidance sectors and make comparison between two intensity-modulated radiotherapy (IMRT) techniques, ``butterfly{''} with three anterior and two posterior beams, and ``rainbow{''} with five anterior beams. Conformity index (CI), homogeneity index MD, organ of risk doses, and monitor unit (MU) values are used as evaluation tools. METHODS IMRT and VMAT plans generated for 15 mediastinal lymphoma patients. Sandglass technique consists of two full arc with avoidance sectors (240 degrees-300 degrees and 60 degrees-120 degrees), butterfly technique with five static fields (0 degrees, 40 degrees, 160 degrees,190 degrees, and 330 degrees), and rainbow technique has five static fields (0 degrees, 20 degrees, 40 degrees, 320 degrees, and 345 degrees). The prescribed treatment dose was 30.6 Gy in 17 fractions. Dosirnetric data were compared using cross-paired sample t-test. RESULTS Lung V5 doses were 41.62-50.74\%, V20 doses were 12.72-16.21\%, heart mean doses were between 454 and 509 cGy, spinal cord max point doses were between 2210 and 2798 cGy, esophagus mean doses were between 1309 and 1409 eGyHI, CI, and MU values were calculated. Lung V20, mean esophagus, and mean heart and spinal cord max. point doses were observed significantly lower at sandglass technique (p=0.001, p=0.02, p=0.013, and p=0.001). CI is significantly better than other two techniques (rainbow p=0.000 and butterfly p=0.001). On the other hand, lung V5 doses significantly lower at rainbow technique (p=0.035), besides, III has significant advantage with respect to others. Sandglass has lower MU value with 484 MU. CONCLUSION Sandglass technique has remarkable advantageous for lung V20, heart, esophagus, spinal cord, CI, and MU. Treatment plans with lower critical organ doses have great importance in terms of late side effects in patients with long survival expectancy. Sandglass plan was preferable for mediastinal lymphoma.
Keywords: Intensity-modulated radiotherapy; lymphoma; mediastinum; volumetric arc therapy